Balance Nutrition Education Through Recipe Books in an Effort to Prevent Wasting in the Work Area of Pardasuka Health Center - Erika Damayanti; Harris Rambey; Rismawati Hutapea; Annisa Kusumawardani; Iis Sulastri (JURNAL PENGMAS KESTRA (JPK), 2026)
Wasting is an acute nutritional problem among children under five that remains a public health challenge in Pringsewu Regency, with a prevalence reaching 11.1%. One of the primary risk factors for this condition is the low knowledge of mothers regarding the principles of balanced nutrition and variations in processing local food. This community service activity (PkM) aims to improve the knowledge of mothers with children under five regarding balanced nutrition through education based on the "PARDASUKA" local recipe book. The method used was direct nutritional education with a pre-test and post-test design involving 32 mothers, accompanied by interactive discussions and the distribution of posters and recipe books. The results showed a significant increase in the participants' knowledge. Before the education, the majority of mothers had poor knowledge at 62.5% (20 people), the good category was 25.0% (8 people), and the excellent category was only 12.5% (4 people). After the intervention, the proportion of poor knowledge decreased drastically to 12.5% (4 people), the good category became 9.37% (3 people), while the excellent category surged sharply to 78.12% (25 people). Overall, there was a recorded increase in knowledge of 65.62%. In conclusion, nutritional education intervention using practical media such as local food-based recipe books is proven effective in significantly increasing mothers' understanding, thereby holding great potential to support sustainable efforts in preventing and reducing wasting rates.